Management in the care of people with HIV in primary health care in times of the new coronavirus - Ianka Cristina Celuppi; Betina Hörner Schlindwein Meirelles; Gabriela Marcellino de Melo Lanzoni; Daniela Savi Geremia; Fernanda Karla Metelski (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To understand management practices in the care of people living with the human immunodeficiency virus (HIV) in primary health care in a Brazilian capital, in times of the new coronavirus (covid-19) pandemic. METHOD Qualitative research, anchored in the methodological-analytical framework of the grounded theory, constructivist aspect. Data were collected by using intensive online interviews with nurses from health centers and managers of the municipal health department. Data collection and analysis occurred concomitantly in two phases of analysis: initial and focused coding. RESULTS They point to the development of best care practices, with emphasis on initiatives for coordination of care, decentralization of clinical management for primary health care services, establishment of protocols and flows, agreement of intersectoral partnerships, use of groups and social networks, use of tools such as teleconsultation and health surveillance spreadsheet and formation of support networks. CONCLUSION The Brazilian capital restructured its network of health services with the implementation of clinical and management protocols, seeking to maintain care for people living with HIV. We highlighted the incorporation of non-face-to-face care technologies and the facilitation of routines, as strategies for expanding access.